COVID-19 vaccination: a systematic review of vaccination strategies based on economic evaluation studies - Samsudin, Khalsom; Mahmud, Aidalina (Malaysian Medical Association, 2023)
Introduction: Countries must employ the most efficient way to vaccinate their population with the COVID-19 vaccines, given the vaccines low availability compared to its demand. This review aims to identify and compare the different COVID-19 vaccine delivery strategies employed internationally in the recent year based on the economic evaluation findings and subsequently to recommend the most cost-effective strategy among them. Material and Methods: A systematic review was conducted by examining online databases (Scopus, MEDLINE and Science Direct) to identify health economic evaluation studies of COVID-19 vaccines. Critical appraisal of studies was conducted using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). Results: A total of nine studies were selected for analysis. Results show two strategies that were cost-effective compared to its comparators: mass vaccination program compared to no vaccination and universal vaccination approach compared to a risk-stratified vaccination approach. Several other strategies were found to increase the cost-consequences in the COVID-19 vaccination program: higher vaccine effectiveness, higher vaccination pace, increased vaccination coverage, and vaccine prioritisation for an at-risk population. The study findings were restricted to analysis based on the current available data. Conclusion: COVID-19 vaccination policies should aim for increased vaccine production as well as a rapid and extensive vaccine delivery system to ensure the maximal value of vaccination strategies. These results can aid policymakers in opting for the most efficient approach to vaccinating the population during this COVID-19 pandemic and future pandemic.